IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Khalimah, Siti Nur; Azra, Zinea Lazuardi; Sari, Fega Kumala; Sari, Selta; Sari, Resti Komala (Journal of Primary Education, 2024)
This study aims to analyze the implementation of the Independent Curriculum in improving the quality of learning at Al-Azhar Elementary School in Bengkulu City. This study will examine how the implementation of the Independent Curriculum and its impact at Al-Azhar Elementary School in Bengkulu City, including in terms of learning planning, learning implementation, and assessment of learning outcomes. This study uses a qualitative research method with a case study approach. Data will be collected through interviews, observations, and documentation. The participants in this study were teachers, students, and principals at Al-Azhar Elementary School in Bengkulu City who have implemented the Independent Curriculum. The results of the study provide a comprehensive of the Independent Curriculum implementation at Al-Azhar Elementary School in Bengkulu City which has a positive impact on the quality of learning such as increasing student learning motivation, increasing student learning outcomes, and developing student competencies that are relevant to the needs of the 21st century.